Fungsi Ritual Barong Nguying di Desa Adat Bebalang Kecamatan Bangli Kabupaten Bangli - Anak Agung Raka Asmariani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Barong Ngunying is one form of Barong dance from many forms and types of Barong dance. Besides Ngunying, Barong also usually begins with a sequence of religious rituals followed by Bapang Barong dance. After Bapang Barong dance is performed, it is assembled withPanglembar dance by taking the Barong Swari play. As the main performance of the event from Barong Ngunying is the meeting between Barong and Rangda which symbolizes the meeting of PurushaPradhana which gives rise to PancaMahaButha. The Panca Maha Butha comes from the sacred power of Barong and Rangda, and furtherget into the human body. This condition causesa Trance which be marked by dancing like a drunken person, namely srayang-sruyung or screaming hysterically, and do not use Balinese dance standards. By performing out the Barong Ngunying ritual, the people of Desa Pakraman Bebalang are protected from calamity and pest until now. This study discusses two problems, including: 1) What is the What is the function of the Barong Ngunying ritual? This research uses theory of religion. This research concludes that the function of the Barong Ngunying ritual is divided into social function, religious function, and aesthetic function.